Find the integral surface passing through the data curve x=1, z=y2+y of the equation x3 zx+y(3x2+y)zy =z(2x2+y)
we have to find the integral surface of the given equation:-
"x^3z_x+y(3x^2+y)z_y=z(2x^2+y)"
It is Lagrange's partial differential equation of type:
"Pp+Qq=R"
So, the
Lagrange's auxiliary equation will be
"\\frac{dx}{x^3}=\\frac{dy}{y(3x^2+y)}=\\frac{dz}{z(2x^2+y)}"
At first we take
"\\frac{dx}{x^3}=\\frac{dy}{y(3x^2+y)}\\\\\\implies\\frac{dy}{dx}=\\frac{y(3x^2+y)}{x^3}\\\\\\implies\\frac{1}{y^2}\\frac{dy}{dx}=\\frac{\\frac{3x^2}{y}+1}{x^3}\\\\\\implies-\\frac{dt}{dx}=\\frac{3t}{x}+\\frac{1}{x^3}\\\\\\implies\\frac{dt}{dx}+\\frac{3t}{x}=-\\frac{1}{x^3}\\\\\\\\\\\\\\\\\\implies tx^3=\\intop(-\\frac{1}{x^3})(x^3)dx\\\\\\implies tx^3=\\intop(-1)dx\\\\\\implies tx^3=-x+c_1\\\\\\implies\\frac{x^3}{y}=-x+c_1.............(1)"
[ let "\\frac{1}{y}=t ;" & the integrating factor "e^(\\intop\\frac{3dx}{x})\\\\"
"\\implies e^(\\ln(x^3))\\\\\\implies x^3" ]
now we will take
"\\frac{dx}{x^3}=\\frac{dy}{y(3x^2+y)}=\\frac{dz}{z(2x^2+y)}\\\\=\\frac {zdy-ydz}{yz(3x^2+y)-yz(2x^2+y)}=\\frac{zdy-ydz}{x^2yz}\\\\\\implies\\frac{dx}{x^3}=\\frac{zdy-ydz}{x^2yz}\\\\\\implies\\frac{dx}{x}=\\frac{zdy-ydz}{yz}\\\\\\implies\\frac{dx}{x}-\\frac{dy}{y}+\\frac{dz}{z}=0\\\\\\implies\\intop\\frac{dx}{x}-\\intop\\frac{dy}{y}+\\intop\\frac{dz}{z}=0\\\\\\implies\\ln\\frac{xz}{y}=\\ln(c_2)\\\\\\implies\\frac{xz}{y}=c_2............(2)"
x=1& z="y^2+y" values are given
putting the values in the equations (1)&(2) we get
"c_1=\\frac{1}{y}+1........(3)\\\\c_2=(y+1).......(4)"
putting the value of y of equation(4) in equation(3) we get
"(c_2-1)(c_1-1)=1\\\\\\implies(\\frac{xz}{y}-1)(\\frac{x^3}{y}+x-1)=1......(5)"
hence the equation (5) is the required integral surface.
Comments
Leave a comment